Riesgo de insolvencia financiera en las PYMES del sector florícola del cantón Latacunga bajo el modelo Z1-Altman - Heredia Reyes, Johana Gabriela (2022)
The objective of this research is to analyze the risk of insolvency of floricultural companies located in the city of Latacunga, province of Cotopaxi between the period 2012-2019 with a total of 13 companies with 8 years of continuous activity, allowing to verify the effectiveness of the model and analyze the financial situation of the companies so that the necessary corrective measures can be taken and avoid falling into possible bankruptcy. With the information obtained, it was identified that during the study the model is a functional tool that can be a good predictor of the financial situation of floriculture; Insolvency and risk measurement is a matter of great importance in the management of companies, and makes them less dependent on situations of market uncertainty, so it must be forecast in advance in order to make decisions on time and thus prevent companies from become bankrupt and have difficulty meeting their current obligations as they fall due. The Z1-Altman statistical model was applied, this being an insolvency prediction model, the study determined that it has a high percentage of bankruptcy risk prediction of companies because the companies with low results with respect to the indicators are the that are more likely to go bankrupt, in the last year of study 6 companies went bankrupt and 7 in the gray zone that represent an alert stage for companies, for which a series of strategies are presented to improve the risk of insolvency of companies in this situation.